SYSTEM AND METHOD FOR DETERMINING A TARGET SUBJECT INTERFACE TEMPERATURE BASED ON A BASELINE TEMPERATURE (2013)
The present disclosure pertains to a pressure support system configured to provide pressure support therapy to a subject, wherein the pressure support system comprises a subject interface heater configured to controllably heat a pressurized flow of breathable gas to a target temperature that is offset from a baseline temperature. The breathable gas baseline temperature target offset ensures the gas delivered to the subject is delivered at a comfortable temperature and/or humidity level that does not cause airway dryness or result in condensed water in the subject interface. In one embodiment, the pressure support system comprises one or more of a pressure generator, a subject interface, a subject interface heater, one or more subject interface temperature sensors, one or more baseline temperature sensors, one or more general sensors, a humidifier, a user interface, a processor, electronic storage, and/or other components.